INCREASED GLYCEMIC LEVEL FAVORS THE GROWTH OF MICOBACTERIUM TUBERCULOSIS MICRO- BACILLI - HEM LATA; SURYA KANT (International Journal of Pharma and Bio Sciences, 2013)
Pulmonary tuberculosis and diabetes mellitus are coexisting frequently. Diabetic patients have an increased tendency to acquire tuberculosis. The frequency of tuberculosis is 4-5 times more aggressive in poorly controlled diabetics and is significantly associated with the development of pleural effusion. Increased reactivation of tuberculosis has also been recorded in diabetics. One hundred and five patients of Diabetes Mellitus (Type-1=3, Type-2=102) with Pulmonary Tuberculosis were enrolled as case group, two hundred and ten patients of only Pulmonary Tuberculosis were enrolled as control group. Assess the clinical, bacteriological radiological images of all enrolled patients were assessed. Sex distribution (male 64.76% vs. 59.05% , female 35.23% vs. 40.95% ). 55.28% of case group were positive for tuberculin skin test and 60.52% of control group were positive for tuberculin skin test. 69.67% patients of case group showed atypical pattern with lower and lower middle lung field involvement. Level of HbA1c 8.99 ±1.07 & AFB 1.51 ± 0.69 in case & level of HbA1c 5.43 ± 0.76 & AFB 1.15 ± 0.50 in control.. Hyperglycemia is significantly correlated with load of micro bacilli (Correlation Coefficient(r)= 0.3321 vs. 0.1294 & p=.0478 vs. p=0.5375 ). Hyperglycemia is strongly associated with severity of fever and haemoptysis. Hyperglycemia is significantly correlated with the load of acid fast micro-bacilli. So theDiabetic patients are more prone for the severity of Pulmonary Tuberculosis. Diabetic patients showed worst condition of lungs and increase the frequency of complications.